Navigating Indonesia’s Economic Crossroads: The Future of State-Owned Enterprises in a Transforming National Economy - Aldehita Purnasanti Maulida; Indah Sri Utari; Yustina Dhian Novita; Abu Bakar Munir (Indonesian Journal of Advocacy and Legal Services, 2026)
Indonesia’s economy is currently positioned at a decisive crossroads, facing the dual pressures of global market volatility and domestic structural transformation. Within this context, state-owned enterprises (BUMN) remain central actors, historically tasked with advancing national development objectives while simultaneously serving as instruments of fiscal stability and political legitimacy. Yet, their future role is increasingly contested as Indonesia seeks to reconcile efficiency, transparency, and competitiveness with broader goals of social equity and sustainable growth. This article critically examines the evolving position of BUMN in Indonesia’s transforming economy by integrating economic performance data, governance reforms, and comparative international perspectives. The analysis highlights a paradox: while BUMN continue to drive infrastructure expansion, energy provision, and financial intermediation, they also generate fiscal vulnerabilities through inefficiency, rent-seeking practices, and governance deficits. Regulatory reforms have sought to modernize corporate structures and enhance accountability, but enforcement remains uneven and institutional fragmentation persists. Drawing on socio-legal and political economy frameworks, the study argues that Indonesia’s economic sustainability depends on reorienting BUMN from state-centric instruments toward engines of innovation, competitiveness, and public value creation. By situating Indonesia’s experience within global debates on state capitalism, corporate governance, and developmental economics, the article contributes to understanding how emerging economies can navigate the tension between market liberalization and state intervention. It emphasizes that the future of BUMN will determine whether Indonesia can transform its current economic crossroads into a pathway toward inclusive, resilient, and globally competitive development. Ultimately, the study underscores that accountability, efficiency, and victim-centered governance are not optional reforms but essential conditions for Indonesia’s long-term economic transformation.